2020
DOI: 10.1101/2020.09.29.20203125
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seroprevalence and Risk Factors of SARS CoV-2 in Health Care Workers of Tertiary-Care Hospitals in the Province of Khyber Pakhtunkhwa, Pakistan

Abstract: Background: High number of SARS CoV2 infected patients has overburdened healthcare delivery system, particularly in low-income countries. In the recent past many studies from the developed countries have been published on the prevalence of SARS CoV2 antibodies and the risk factors of COVID 19 in healthcare-workers but little is known from developing countries. Methods: This cross-sectional study was conducted on prevalence of SARS CoV2 antibody and risk factors for seropositivity in HCWs in tertiary care hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Like, the study reported that the high prevalence rate of COVID-19 in health-care professionals is partly attributed to the lack of adequate supply of PPE to health-care workers. 18 The findings of our study are also fully aligned with the finding reported by Ranney et al 19 Whereas, COVID-19 is surrounded by many uncertainties in terms of its place of origin, etiology, clinical features, mortality rates, morbidity rates, risk prevention strategies, etc., this study is of paramount importance, as it will initiate a debate among the policy-makers and concerned stakeholders to take into account the protection of nurses and paramedics with the existing recommended preventive measures as well as the launch of additional interventions to make sure that a package comprising the adequate supply of PPE, tailored infection prevention and control training, and access to updated personal protection protocols by the WHO is made available to them.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Like, the study reported that the high prevalence rate of COVID-19 in health-care professionals is partly attributed to the lack of adequate supply of PPE to health-care workers. 18 The findings of our study are also fully aligned with the finding reported by Ranney et al 19 Whereas, COVID-19 is surrounded by many uncertainties in terms of its place of origin, etiology, clinical features, mortality rates, morbidity rates, risk prevention strategies, etc., this study is of paramount importance, as it will initiate a debate among the policy-makers and concerned stakeholders to take into account the protection of nurses and paramedics with the existing recommended preventive measures as well as the launch of additional interventions to make sure that a package comprising the adequate supply of PPE, tailored infection prevention and control training, and access to updated personal protection protocols by the WHO is made available to them.…”
Section: Discussionsupporting
confidence: 91%
“…This study is a part of a larger study (N = 1012) 18 by the investigators that aim at studying seroprevalence for COVID-19 among the various health-care providers working in a set of 3 selected public and private sector teaching hospitals of Peshawar, Pakistan. The larger study (not published yet) has found a comparatively very high prevalence among nurses and paramedics.…”
Section: Methodsmentioning
confidence: 99%
“…Conducted at a hospital/healthcare clinic/ICU Younas, [142] Pakistan-Karachi, Sindh Conducted among blood donors Ali, [143] Pakistan-Khyber Pakhtunkhwa Focuses on patient cohort Haq, [144] Pakistan-Khyber Pakhtunkhwa Focuses on healthcare workers Javed, [145] Pakistan…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Conducted at a hospital/healthcare clinic/ICU Younas, [142] Pakistan-Karachi, Sindh Conducted among blood donors Ali, [143] Pakistan-Khyber Pakhtunkhwa Focuses on patient cohort Haq, [144] Pakistan-Khyber Pakhtunkhwa Focuses on healthcare workers Javed, [145] Pakistan-multiple cities across Pakistan Focuses on working individuals Nisar, [146, p. 2] Pakistan-Peshawar Conducted among blood donors Jeewandara, [147] Sri Lanka-Colombo, Western Province Focuses on asymptomatic individuals . CC-BY 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: -36mentioning
confidence: 99%